Characterization of irreversible physio-mechanical processes in stretched fetal membranes. (15th January 2016) - Marom, Yulia; Goldman, Shlomit; Shalev, Eliezer; Shilo, Doron
Graphical abstract: Abstract: We perform bulge tests on live fetal membrane (FM) tissues that simulate the mechanical conditions prior to contractions. Experimental results reveal an irreversible mechanical behavior that appears during loading and is significantly different than the mechanical behavior that appears during unloading or in subsequent loading cycles. The irreversible behavior results in a residual strain that does not recover upon unloading and remains the same for at least 1 h after the FM is unloaded. Surprisingly, the irreversible behavior demonstrates a linear stress–strain relation. We introduce a new model for the mechanical response of collagen tissues, which accounts for the irreversible deformation and provides predictions in agreement with our experimental results. The basic assumption of the model is that the constitutive stress–strain relationship of individual elements that compose the collagen fibers has a plateau segment during which an irreversible transformation/deformation occurs. Fittings of calculated and measured stress–strain curves reveal a well-defined single-value property of collagenous tissues, which is related to the threshold strain εth for irreversible transformation. Further discussion of several physio-mechanical processes that can induce irreversible behavior indicate that the most probable process, which is in agreement with our results for εth, is a phase transformation of collagen molecules from an α-helix to a β-sheet structure. A phase transformation is a manifestation of a significant change in the molecular structure of the collagen tissues that can alter connections with surrounding molecules and may lead to critical biological changes, e.g., an initiation of labor. Statement of Significance: This study is driven by the hypothesis that pre-contraction mechanical stretch of the fetal membrane (FM) can lead to a change in the microstructure of the FM, which in turn induces a critical biological (hormonal) change that leads to the initiation of labor. We present mechanical characterizations of live FM tissues that reveal a significant irreversible process and a new model for the mechanical response of collagen tissues, which accounts for this process. Fittings of calculated and measured results reveal a well-defined single-value property of collagenous tissues, which is related to the threshold strain for irreversible transformation. Further discussion indicates that the irreversible deformation is induced by a phase transformation of collagen molecules that can lead to critical biological changes.